Co-formation and co-release of genotoxic PAHs, alkyl-PAHs and soot nanoparticles from gasoline direct injection vehicles. (April 2018) - Muñoz, Maria; Haag, Regula; Honegger, Peter; Zeyer, Kerstin; Mohn, Joachim; Comte, Pierre; Czerwinski, Jan; Heeb, Norbert V.
Abstract: Gasoline direct injection (GDI) vehicles quickly replace traditional port-fuel injection (PFI) vehicles in Europe reaching about 50 million vehicles on roads in 2020. GDI vehicles release large numbers of soot nanoparticles similar to conventional diesel vehicles without particle filters. These exhausts will increasingly affect air quality in European cities. We hypothesized that such particles are released together with polycyclic aromatic hydrocarbons (PAHs) formed under the same combustion conditions. Emission data of a fleet of 7 GDI vehicles (1.2–1.8 L) including Euro-3, -4, -5 and -6 technologies revealed substantial particle emissions on average of 2.5 × 10 12 particles km −1 in the cold worldwide harmonized light vehicle test cycle (cWLTC), the future European legislative driving cycle. Particle emissions increased 2–3 orders of magnitude during acceleration like CO, indicating that transient driving produces fuel-rich conditions with intense particle formation. For comparison, an Euro-5 diesel vehicle (1.6 L) equipped with a particle filter released 3.9 × 10 10 particles km −1 (cWLTC), clearly within the Euro-5/6 limit value of 6.0 × 10 11 particles km −1 and 64-fold below the GDI fleet average. PAH and alkyl-PAH emissions of the GDI vehicles also exceeded those of the diesel vehicle. Mean GDI emissions of 2-, 3-, 4-, 5- and 6-ring PAHs in the cWLTC were 240, 44, 5.8, 0.5 and 0.4 μg km −1, those of the diesel vehicle were only 8.8, 7.1, 8.6, 0.02 and 0.02 μg km −1, respectively. Thus mean PAH emissions of the GDI fleet were 2 orders of magnitude higher than the bench mark diesel vehicle. A comparison of the toxicity equivalent concentrations (TEQ) in the cWLTC of the GDI fleet and the diesel vehicle revealed that GDI vehicles released 200–1700 ng TEQ m −3 genotoxic PAHs, being 6–40 times higher than the diesel vehicle with 45 ng TEQ km −1 . The co-release of genotoxic PAHs adsorbed on numerous soot nanoparticles is critical due to the Trojan horse effect describing the property of sub-200 nm particles being deposited in the alveoli transporting genotoxic compounds into the lung. These nanoparticles are persistent and may eventually penetrate the alveolar membrane reaching the blood circulation system. We showed that all GDI vehicles tested released large numbers of nanoparticles carrying substantial loads of genotoxic PAHs. If non-treated diesel exhaust is considered as class-1 carcinogen by the WHO inducing lung cancer in humans, these GDI vehicle exhausts may be a major health risk too for those exposed to them corroborating the progress achieved with current diesel vehicles, now equipped with efficient particle filters. Highlights: GDI vehicles release substantial numbers of persistent soot-like nanoparticles. PN emissions of GDI fleet were 60–700-fold higher than in the diesel vehicle with DPF. PN and CO emissions increase up to three orders of magnitude during acceleration. Genotoxic PAH emissions were 6–40-fold higher than in the diesel with DPF. Inhalation of soot nanoparticles carrying genotoxic PAHs poses major health threat.